Bibliometric Analysis of International Publications Trend on The Taliban - Anisa Indraningtyas; Gonda Yumitro (Institut Agama Islam Negeri Salatiga, 2022)
This research aims to navigate the result of international publication trends regarding the Taliban for 27 years, starting from 1994 to 2021, utilizing a bibliometric analysis study that analyzed trends in international publications based on quantitative data sources obtained through one of the Scopus data search engines. In addition, bibliometric analysis in this study employed a data visualization software VOSviewer to analyze keywords that often appear in research data regarding the trend of international publications of the Taliban. The findings in this bibliometric analysis study indicated three outcomes. Firstly, numerous international publications on the Taliban as a research topic were navigated, accounting for 1,538 publication documents based on the Scopus data search engine with the keyword